2020
DOI: 10.3390/su12051761
|View full text |Cite
|
Sign up to set email alerts
|

Decelerations of Passenger Vehicles on Gravel Arrester Beds

Abstract: Gravel-filled arrester beds, also called safety-escape ramps or vehicle run-out areas, have long been a road-safety feature for safely stopping heavy road vehicles from running off the road. In the recent past, there has been consideration given to installing these features on highway access ramps to provide safe areas to stop passenger cars driving at highway speeds. The work presented in this article was performed to investigate the behaviour of standard-size passenger cars on gravel-filled arrester beds, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The use of aggregate (19/50 mm range [15]), gravel or crushed, is a common feature for truck arrestor beds, when the wheels must displace well the material and sink inside it, with more favorable results for round aggregates due to its small friction angle [16], [17]. Round aggregates cause a high and quick deacceleration [18]; recent studies for passengers' vehicles have shown values of 0.3 g and 0.9 g for, respectively, coasting vehicles and in braking action [19]. However, in opposite to traditional and efficient use of round gravels in truck arrestor, aggregate spray launched to dissipate energy can be a major concern since one can foresee the aircraft fuselage damage risks due to gravel launchings during an overrun, besides the unavoidable risks for the gears systems.…”
Section: Engineered Materials Arresting Systems For Airportsmentioning
confidence: 99%
“…The use of aggregate (19/50 mm range [15]), gravel or crushed, is a common feature for truck arrestor beds, when the wheels must displace well the material and sink inside it, with more favorable results for round aggregates due to its small friction angle [16], [17]. Round aggregates cause a high and quick deacceleration [18]; recent studies for passengers' vehicles have shown values of 0.3 g and 0.9 g for, respectively, coasting vehicles and in braking action [19]. However, in opposite to traditional and efficient use of round gravels in truck arrestor, aggregate spray launched to dissipate energy can be a major concern since one can foresee the aircraft fuselage damage risks due to gravel launchings during an overrun, besides the unavoidable risks for the gears systems.…”
Section: Engineered Materials Arresting Systems For Airportsmentioning
confidence: 99%
“…Incidents on the road often result in unpredictable consequences, including a series of losses involving rescue personnel, vehicles, and road safety measures after the collision [4]. Among these accidents, loss of vehicle control is one of the critical reasons for serious crashes, and vehicle braking problems is one of the 10 key factors leading to the loss of vehicle control [5].…”
Section: Introductionmentioning
confidence: 99%
“…Miha Ambrož used a passenger car to carry out a real vehicle test of emergency stop in truck escape ramps. According to the test results, they concluded that: when the roundness of the aggregate particles of the arrester bed is large and the particle size is small, the deceleration after the vehicle enters is greater [17]. Filippo A et al made deformable units through cementitious materials to replace the gravel aggregate of the traditional truck escape ramps.…”
Section: Introductionmentioning
confidence: 99%